Red blood cell folate and visceral adipose tissue among young and middle-aged American adults - Jiang, Chaohui; Li, Jianfen; Yu, Haiyan; Luo, Xingda; Wu, Lingfeng; Long, Qilian; Zhang, Bin (Frontiers in Nutrition, 2025)
BackgroundThe relationship between red blood cell (RBC) folate levels and visceral adipose tissue (VAT) accumulation has not been well-explored. This study investigates the association between RBC folate and VAT in young and middle-aged adults in the United States.MethodsA cross-sectional analysis was conducted using data from 7,591 individuals aged 20 to 59 years, drawn from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. VAT was measured using dual-energy X-ray absorptiometry (DXA). RBC folate levels were quantified using a multi-step process combining microbiologic assays and liquid chromatography–tandem mass spectrometry (LC–MS/MS). Multivariate linear regression models were applied to assess the relationship between RBC folate and VAT mass.ResultsAfter adjusting for potential confounders, RBC folate levels were positively associated with VAT mass, with a β coefficient (95% CI) of 0.05 (0.03, 0.07). A J-shaped dose–response relationship was observed (nonlinear, p < 0.001), with a threshold effect identified at an RBC folate level of 397.18 ng/mL. Below this threshold, the association was negative [β (95% CI): −0.10 (−0.20, −0.01)], while above the threshold, the association became positive [β (95% CI): 0.06 (0.03, 0.09)].ConclusionThe association between RBC folate and VAT mass in young and middle-aged American adults follows a J-shaped curve, with a threshold effect observed at an RBC folate level of 397.18 ng/mL. Further research is needed to explore the underlying mechanisms of this association.